1990
DOI: 10.1203/00006450-199004000-00015
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Maternal Starvation on Plasma Insulin-Like Growth Factor I Concentrations in the Late Gestation Ovine Fetus

Abstract: ABSTRACT. In view of the suggested relationship between substrate availability, fetal growth and circulating fetal IGF-I concentrations, we investigated the effect of maternal starvation on plasma IGF-I levels in the late gestation ovine fetus. Ten fetuses aged 125-130 d gestation were sampled daily from indwelling arterial catheters. Ewes were starved for 72 h. Starvation was terminated with an intravenous infusion of 10% glucose to the ewe. Food was then replaced 4 h later. Fetal IGF-I concentrations fell fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 20 publications
(25 reference statements)
2
15
1
Order By: Relevance
“…The absence of an effect of nutrition on fetal profiles of IGF-I and insulin contrasts with previous reports involving acute undernutrition/starvation during pregnancy (Schreiner et al 1980, Bassett et al 1990. This difference in response between experiments probably reflects the difference in the pattern of undernutrition, and highlights the different effects of acute and chronic undernutrition.…”
Section: Discussioncontrasting
confidence: 54%
“…The absence of an effect of nutrition on fetal profiles of IGF-I and insulin contrasts with previous reports involving acute undernutrition/starvation during pregnancy (Schreiner et al 1980, Bassett et al 1990. This difference in response between experiments probably reflects the difference in the pattern of undernutrition, and highlights the different effects of acute and chronic undernutrition.…”
Section: Discussioncontrasting
confidence: 54%
“…The circulating IGF-I levels in the fetus showed a similar response to maternal fasting as that seen in postnatal animals [19,20]. This was also observed in rat and other ovine maternal/fetal models [30][31][32].…”
Section: Effect Of Igf-i Infusionsupporting
confidence: 62%
“…Acute hypoxia has been reported to stimulate the circulating RAS, although nothing is known about its effects on the fetal intrarenal RAS (Wood, 1995). Placental restriction also causes fetal hypoglycaemia (Phillips et al 1997), which is also associated with low levels of insulin-like growth factor-1 (IGF-1) levels (Bassett et al 1990;Owens et al 1994;Kind et al 1995). We have recently shown that exogenous infusions of IGF-1 stimulate the activity of the circulating RAS (Marsh et al 1998) and activate renin gene expression and synthesis (A.…”
Section: Discussionmentioning
confidence: 99%